2019
DOI: 10.2135/cropsci2019.03.0198
|View full text |Cite
|
Sign up to set email alerts
|

Forage Accumulation, Nutritive Value, and Botanical Composition of Grass–Cicer Milkvetch Mixtures under Two Harvest Managements

Abstract: Limited information is available on cicer milkvetch (CMV, Astragalus cicer L.) performance in mixtures with grasses. A field trial was sown at Melfort, SK, Canada, in May 2013 to evaluate forage accumulation, nutritive value, and botanical composition of different mixtures of grasses and CMV under two‐cut and three‐cut harvest management from 2014 to 2017. Thirteen forage mixtures consisted of (i) monocultures of Bromus riparius Rehm. (MB), Bromus riparius Rehm. × B. inermis Leyss. (HB), Agropyron cristatum (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…Our study revealed that the grass-legume mixtures did not improve annual herbage accumulation over the grass monoculture, and concurred with the results reported by Minneé et al [65] but differs from those of Berdahl et al [66] and Cox et al [52]. Some possible reasons for the observed trends in our study could be the utilization of a two-cut system that can reduce either the grass or legume component in the sward due to shading as against more frequent harvest [40]. Additionally, the duration of the study did not allow the grass component in the sward to fully utilized the N fixed by the legume component, which may have been hampered by the mineralization process.…”
Section: Herbage Accumulationsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study revealed that the grass-legume mixtures did not improve annual herbage accumulation over the grass monoculture, and concurred with the results reported by Minneé et al [65] but differs from those of Berdahl et al [66] and Cox et al [52]. Some possible reasons for the observed trends in our study could be the utilization of a two-cut system that can reduce either the grass or legume component in the sward due to shading as against more frequent harvest [40]. Additionally, the duration of the study did not allow the grass component in the sward to fully utilized the N fixed by the legume component, which may have been hampered by the mineralization process.…”
Section: Herbage Accumulationsupporting
confidence: 90%
“…However, in water-scarce environments, single species cultivation of forage crops may pose a threat to the longevity of crop stand, and thus, forage species mixtures are deemed a more reliable choice [37]. Cultivating mixtures of forage species have been shown to increase overall forage biomass production and nutrient content compared to monocultures [38][39][40] as a result of niche complementarity [41]. For example, root morphological traits differ among forage species, and in mixed swards, it allows for an increase in nutrient uptake from different soil nutrient pools compared to monocultures because of complementary root distribution [42].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Goplen et al [39], July NovaSF-grass yield at SASK (5.4 Mg ha −1 ) in the current study, had similar biomass, however September yield was lower (4.4 Mg ha −1 ). Yield of CMV with MBG or HBG at Melfort, SK [11] was higher than the current study CMV-grass (11 vs. 7.5 Mg ha −1 at SASK), likely due to the site difference (Black Chernozem soil and high rainfall) and cultivar selection (Oxley II CMV and Fleet MBG). July CMVgrass mixtures at SWIFT accumulated greater or similar DMY to Oxley CMV-grass species (Swift RWR and Fleet MBG, yielding 1.3 and 1.7 Mg ha −1 , respectively) in a 7-yr study [34].…”
Section: Forage Yieldcontrasting
confidence: 73%
“…Soil-climatic conditions influenced yield ranging 9.7 to 90% between the harvest dates, with greater biomass in July than in September. Foster et al [11] reported greater mixture yield at mid-July compared to mid-September, although it was in a moister site-Melfort, SK, Canada. The current study differs for ALF, SF, and CMV-grass fall yields from a Brown soil study at SWIFT [34].…”
Section: Forage Yieldmentioning
confidence: 96%
See 1 more Smart Citation